Factors Affecting the English Reading Literacy of Junior High School Students - Ika Sulis Setianingsih (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
This study aims at finding out how: (1) amount of input, (2) amount of vocabulary, (3) learner’s motivation, (4) amount of input, amount of vocabulary, and learner’s motivation affect the English reading literacy; (5) amount of input affects amount of vocabulary, (6) amount of vocabulary affects learner’s motivation, and (7) amount of input affects learner’s motivation. This study was an ex-post facto. The population comprised year VII students of SMP’s in Bantul District in the second semester of the academic year of 2013/2014. A sample of 384 students was established using the proportional sampling technique. The data were collected through a close-ended questionnaire and test. The close-ended questionnaire was used to collect the data related to students’ learning input and motivation. The test was used to find out the students’ knowledge on vocabulary and reading comprehension. The data were analyzed by employing the linear regression analysis for the linear variables, continued by the multiple regression analysis for the whole variables, and then followed by partial correlation. The findings showed that there is a significant effect of: (1) amount of input; (2) amount of vocabulary; (3) amount of inputs, the learner’s motivation, and amount of vocabulary; (4) amount of inputs and learner’s motivation; (5) learner’s motivation and amount of vocabulary; and (6) amount of inputs and amount of vocabulary on the English reading literacy of SMP students in Bantul District. Meanwhile, there is no significant effect of learner’s motivation on the English reading literacy of SMP students in Bantul District.